The Role of Adaptive Management in Ensuring Enterprises’ Sustainable Development - HURZHYI, Nataliia; ROZOVYK, Igor; KHARCHENKO, Tetiana; KOBETS, Serhii; KOMANDROVSKA, Veronika (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025DO - 10.14505/tpref.v16.1(33).20, 2025)
I n an ever-evolving business landscape, designing adaptive management systems and agile business models emerges as a pivotal element in guaranteeing companies’ enduring growth and competitiveness in the long term. The aim of the study is to examine the role of adaptive management in ensuring the enterprise’s stable development in a changing business environment. The study utilized empirical methods such as: experimental method, questionnaire method, analysis method, control method based on key performance indicators and modeling method. The mechanism of adaptive management of the enterprise has been developed and tested within the framework of the training course. The author's model of manufacturing enterprises’ adaptive management via the introduction of digital tools into the business model of sustainable development is presented. The survey results demonstrated that the implementation of adaptive management helped their companies achieve key performance indicators. Namely: strategic - 79%, operational - 81%, financial - 76%, production - 84%, marketing - 86%, HR - 77%. The expediency of introducing an adaptive approach to management was confirmed by 93% of respondents. The practical significance of the study lies in the presented model of adaptive enterprise management. It can serve as the basis for the development of sustainable development programs in the context of Industry 4.0.